Assessment of electrical energy use efficiency in Nigeria food industry - Aderemi, A.O.; Aderemi, Helen olubunmi; Ilori, M.O.; Akinbami, john -felix kayode (IEEE, 2023)
African Journal of Food Science. Vol. 3,Issue No.8, pp. 206-216